Of Roads Less Traveled : Assessing the Potential of Economic Migration to Provide Overseas Jobs for Nigeria’s Youth - Adhikari, Samik; Chaudhary, Sarang; Ekeator, Nkechi Linda (World Bank, Washington, DC, 2021)
Nigerians are not only creating a vibrant and dynamic society within Nigeria but are also leaving their footprint across the globe in diverse fields ranging from medicine to movies, and from literature to diplomacy. The main purpose of this report is to aid discussion on creating new labor migration pathways for overseas employment of Nigerians. It aims to support the Government of Nigeria in filling critical information gaps to comprehensively shed light on the issue of international migration. Using available data from secondary sources, it places international migration within the broader labor market context in Nigeria, carefully stressing the push and pull factors that lead to both regular and irregular migration and makes the case for why more structured regular migration will be one of the crucial ways in which Nigeria can support education to work transition for young and aspiring Nigerian jobseekers. The report synthesizes the available evidence to understand the stock and flows of international migrants from Nigeria, major countries of destination, and key areas of vulnerabilities while identifying gaps in evidence to inform decision-making. The final contribution of this report is that it comprehensively assesses the institutional framework governing labor migration at the Federal level in Nigeria, underscoring the various stakeholders involved in the process, and underlining key gaps that are hampering Nigeria’s ability to enhance the benefits and reduce the costs from international migration. This report is structured in three parts. The first part looks at the broader labor market setting in Nigeria, along with the economic and demographic context, to highlight specific drivers of increased migratory pressure in recent years before postulating that the recent surge in irregular migration is a direct consequence of worsening joblessness combined with lack of regular channels for youth to find employment in other countries. The second part presents an analysis of the trends and patterns of international migration from Nigeria to provide insights on the characteristics of international migrants and their contribution to Nigeria’s economy. The third and final part highlights how international migration is increasingly being used as an employment strategy by developing countries and how despite the significant increase in remittance inflows, there is lack of an organized structure that promotes better migration management and facilitates safe and remunerative migration from Nigeria.